Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial melalui Penerapan Keterampilan Proses pada Siswa Sekolah Dasar - Aulia Eka Putri; Suardi Suardi (Universitas Cokroaminoto Palopo, 2023)
This study aims to improve social studies learning outcomes by applying a process skills approach to fifth grade students at SD Negeri 30 Sumpang Bita. This study uses classroom action research (Classroom Action Research) consisting of 2 cycles. Each cycle has four stages, which consist of: planning, action, observation and reflection. Observation sheets and learning outcomes tests are used as research instruments. Observations, learning outcomes tests and documentation used in data collection techniques. Quantitative and qualitative analysis techniques were used in data analysis. The results showed that the first cycle got an average score of 64.7, the second cycle scored higher student learning outcomes, namely the average value reached 86.7. Only 7 students (41%) achieved completeness in cycle I. In contrast to cycle II, there were 16 (96%) students who achieved completeness. This means that classical learning mastery is achieved in cycle II, because the number of students is more than 80%. Thus it was concluded that the application of the process skills approach to social science subjects could improve student learning outcomes.